2021
DOI: 10.1364/oe.432601
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and switchable terahertz polarization converter based on graphene metasurfaces

Abstract: In this work, we propose broadband and switchable terahertz (THz) polarization converters based on either graphene patch metasurface (GPMS) or its complementary structure (graphene hole metasurface, GHMS). The patch and hole are simply cross-shaped, composed of two orthogonal arms, along which plasmonic resonances mediated by Fabry-Perot cavity play a key role in polarization conversion (PC). An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…New nano-sized electronic and electromagnetic components and devices such as antennas, flexible electronic devices, touch screens and high-speed transistors are examples of the states of the art in the graphene world. The unique properties of graphene are due to its gapless electronic band structure 7 10 .…”
Section: Introductionmentioning
confidence: 99%
“…New nano-sized electronic and electromagnetic components and devices such as antennas, flexible electronic devices, touch screens and high-speed transistors are examples of the states of the art in the graphene world. The unique properties of graphene are due to its gapless electronic band structure 7 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve multi-functional metamaterial structures, most of the previously reported graphene-based metamaterial structures are used to achieve the LTC and LTL functions simultaneously [105][106][107][108][109][110][111][112][113][114]. These metamaterial structures can realize multi-frequency or broad-band LTL and LTC polarization conversion in a single metamaterial device.…”
Section: Graphene-based Multi-functional Metamaterials Polarization C...mentioning
confidence: 99%
“…For single-layer discrete graphene patterns, many classical structures, including graphene patches [118], cross double-ellipse graphene patch [107], cross-shaped graphene patch [109], graphene ribbons [110,115], graphene disk with a hollow rectangle [108], graphene split-ring resonator [117], and so on, are used to achieve the polarization conversion function. In this case, Z. Liu et al demonstrated that a layer of ion-gel lies on the top of graphene layer to serve as a transparent spacer layer, forming high capacitive properties between the top metal gate contacts and the underlying layer of the graphene microstructures [117].…”
Section: Graphene-based Multi-functional Metamaterials Polarization C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite important advances in the exploration of the active control of polarization, electrical control of THZ chiral polarization remains largely elusive and suffers from a limited dynamic range of polarization conversion and limited response frequency bandwidth. Because of the highly tunable conductivity in the THz region, two-dimensional (2D) materials (e.g., graphene and black phosphorus) show great potential in THz modulation. Combining graphene with metamaterials/metasurface, electrical modulation of the polarization state of THz beams has been widely demonstrated. However, the working frequency is limited at a certain narrowband because of the resonance nature of metamaterials.…”
Section: Introductionmentioning
confidence: 99%